2000
DOI: 10.1002/(sici)1097-4628(20000516)76:7<1093::aid-app13>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization and addition of styrene andN-phenylmaleimide in the presence of nitroxide

Abstract: ABSTRACT:The copolymerization and addition reaction of styrene (S) with N-phenylmaleimide (PMI), either neat or in xylene, have been found to proceed at 125°C in the presence of 2,2,6,6-tetramethylpiperidin-1-yloxy (TEMPO) radicals. TEMPO-terminated alternating S-PMI copolymers and comonomer adducts were obtained. The amounts of the low molecular weight compounds increased with the increasing content of PMI in the initial mixture. The reaction suggests formation of monofunctional unimolecular initiators. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…[65] Shortly after, the same group described the NMP of styrene and MAh. [66] In these two examples, TEMPO was used as control agent (i.e., first generation nitroxide) and therefore the molecular weight distributions of the formed alternating copolymers were relatively broad. It was demonstrated that a better control can be obtained using RAFT, [67][68][69] ATRP [70] or nitroxides of the second generation.…”
Section: Controlled Radical Copolymerization Of Styrene and Strong Elmentioning
confidence: 99%
“…[65] Shortly after, the same group described the NMP of styrene and MAh. [66] In these two examples, TEMPO was used as control agent (i.e., first generation nitroxide) and therefore the molecular weight distributions of the formed alternating copolymers were relatively broad. It was demonstrated that a better control can be obtained using RAFT, [67][68][69] ATRP [70] or nitroxides of the second generation.…”
Section: Controlled Radical Copolymerization Of Styrene and Strong Elmentioning
confidence: 99%
“…Recently, we have reported the results concerning poly( N ‐butyl‐ or N ‐phenylmaleimide‐ co ‐styrenes) and derived block copolymers (i.e., polymers with incorporated heterocyclic derivatives of 1,2‐ dicarboxyethene), which were synthesized by using the nitroxide technique. 29, 30 Nitroxide‐mediated polymerization leading to the copolymers of maleic anhydride was described by Hawker et al 26, 31 The aim of our present work was to prepare TEMPO‐ terminated copolymers of S with another 1,2‐substituted ethene, diethyl fumarate, and to employ them as macroinitiators in the synthesis of related poly(styrene‐ co ‐diethyl fumarate)‐ block ‐polystyrene copolymers (Scheme ).…”
Section: Introductionmentioning
confidence: 89%
“…On the one hand, the initial "synergistic" effect implies a diffusion control of the degradation products of the COBAMI counit from the more stable St co-unit. On the other hand, reactive species from COBAMI counit would be able to modify the degradation mechanism of St counit which acceleration began to be detected at about 380 ± C. A greater residue than that expected from simulation can also result from the polymer chain ends containing TEMPO [25].…”
Section: Thermal Properties Of Cobami-st Copolymersmentioning
confidence: 98%
“…Copolymerizations of N-alkyl-or N-phenylmaleimides with St in bulk or solution by 'controlled' / living radical polymerization methods like ATRP [20,21] or SFRP [22][23][24][25][26] revealed that alternating copolymers or block copolymers with controlled molecular weight and low polydispersities can be prepared.…”
Section: Copolymerization Of Maleimide Monomer Cobami With Stmentioning
confidence: 99%